Preparation method and application of synergistic flame retardant

By preparing a high-crystallinity boehmite and alumina complex and mixing it with low-crystallinity boehmite, the problem of high-crystallinity boehmite easily aggregating in plastics is solved, the flame retardant properties of thermoplastics are improved, a dense carbon layer is formed to isolate heat exchange, and the flame retardant effect is enhanced.

CN119529383BActive Publication Date: 2025-09-09ANHUI JIANGHUAI AUTOMOBILE GRP CORP LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411782546.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-09-09
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Highly crystalline boehmite tends to aggregate in plastics, affecting their flame retardant properties.

Method used

By preparing a high-crystallinity boehmite and alumina composite and mixing it with porous low-crystallinity boehmite, a boehmite/alumina composite is formed. It is applied to thermoplastics to prevent aggregation and form a dense carbon layer to block heat exchange during combustion.

Benefits of technology

It improves the flame retardant properties of thermoplastics, prevents the aggregation of boehmite/alumina complexes, forms a denser carbon layer, isolates heat exchange, and enhances the flame retardant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the field of polymer material technology, and specifically relates to a preparation method and application of a synergistic flame retardant. This technical solution uses alumina, high-crystallinity boehmite, and low-crystallinity boehmite to prepare a composite material through a specific preparation method. In this technical solution, the prepared alumina is first compounded with high-crystallinity boehmite, and then mixed with porous low-crystallinity boehmite. Under the action of ultrasound, part of the high-crystallinity boehmite / alumina composite enters the pores of the low-crystallinity boehmite to form a boehmite / alumina composite. When applied to thermoplastic plastic materials, part of the thermoplastic plastic material also enters the pores of the low-crystallinity boehmite, thereby preventing the aggregation of the boehmite / alumina composite. When combustion occurs, the thermoplastic forms a denser carbon layer through the framework of the boehmite / alumina composite, blocking heat exchange and improving flame retardant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and in particular relates to a preparation method and application of a synergistic flame retardant. Background Art

[0002] Flame retardancy is one of the important properties of automotive interior and exterior trims, plastic housings, etc. There are many ways to improve the flame retardancy of polymers. In current technology, the flame retardancy of plastics is improved by adding flame retardants and / or synergistic flame retardants to plastics.

[0003] In current technology, boehmite is commonly used as a synergistic flame retardant because boehmite is divided into two categories: high-crystallinity boehmite and low-crystallinity boehmite. Among them, high-crystallinity boehmite has a layered crystal structure, each layer is composed of AlO6 octahedrons, and the center of the octahedron is composed of a double-layer structure formed by positively charged Al3+. The surface of the layered structure contains a large number of hydroxyl groups, and the layers are connected by hydrogen bonds between the hydroxyl groups, forming an ordered layered structure. At the same time, it has a low specific surface area and complete grains, and is used in the field of flame retardants. Low-crystallinity boehmite is used in the field of catalyst supports and adsorption due to its large specific surface area and high porosity. However, due to its small specific surface area, high-crystallinity boehmite, although used in the field of flame retardants, will aggregate in plastics, affecting the flame retardant properties of plastics. Summary of the Invention

[0004] The object of the present invention is to provide a preparation method and application of a synergistic flame retardant to solve the problems existing in the above-mentioned background technology due to the use of high-crystallinity boehmite as a synergistic flame retardant.

[0005] To achieve the above objectives, this application is implemented through the following technical solutions:

[0006] A method for preparing a synergistic flame retardant comprises the following steps:

[0007] S1. Weigh a certain amount of basic aluminum chloride, potassium hydroxide, ether, and deionized water, add them to a reaction vessel, and react at 60-80°C for 3-5 hours to obtain solution A;

[0008] S2. Filter solution A, wash, dry, and then calcine at 720-780°C for 10-12 hours to obtain alumina;

[0009] S3, weighing a certain amount of high crystallinity boehmite, grinding it into powder, and passing it through a 500-mesh sieve to obtain high crystallinity boehmite powder; weighing a certain amount of low crystallinity boehmite, grinding it into powder, and passing it through a 350-mesh sieve to obtain low crystallinity boehmite powder;

[0010] S4. Weigh a certain amount of alumina, high-crystallinity boehmite powder, ether, and deionized water, add them to a reaction vessel, and react at 60-80° C. for 6-8 hours to obtain solution B;

[0011] S5. Filter solution B, wash it, and place it in a vacuum drying oven at 60-80° C. for 8-12 hours to obtain a high-crystallinity boehmite / alumina composite;

[0012] S6. Grinding the high crystallinity boehmite / alumina composite into powder, and passing the powder through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder;

[0013] S7. Add a certain amount of high crystallinity boehmite / alumina composite powder, low crystallinity boehmite powder, ether, and deionized water to a reaction dish, and ultrasonically react at 60-80° C. for 6-8 hours to obtain solution C;

[0014] S8. Filter solution C, wash it, and place it in a vacuum drying oven at 60-80° C. for 8-12 hours to obtain a synergistic flame retardant.

[0015] Furthermore, in step S1, the mass ratio of basic aluminum chloride, potassium hydroxide, ether, and deionized water is (20-30): (16-24): (30-36): (62-72).

[0016] Furthermore, in step S4, the mass ratio of alumina, high crystallinity boehmite powder, ether, and deionized water is (8-12): (40-50): (50-60): (70-90).

[0017] Furthermore, in step S7, the mass ratio of high crystallinity boehmite / alumina composite powder, low crystallinity boehmite powder, ether, and deionized water is: (5-10): (30-50): (50-60): (90-100).

[0018] Furthermore, the ultrasonic reaction in step S7 is 30 KHz.

[0019] Furthermore, in step S8, the mass ratio of high crystallinity boehmite to low crystallinity boehmite is 1:2-1:5.

[0020] An application, use of the synergistic flame retardant prepared by any of the above methods in thermoplastic composite materials.

[0021] Furthermore, a thermoplastic plastic composite material is composed of the following components by weight: 90-110 parts of thermoplastic plastic, 16-18 parts of decabromodiphenylethane, 4-6 parts of synergistic flame retardant, and 0.1-0.5 parts of antioxidant.

[0022] Furthermore, the thermoplastic plastic composite material is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate, and polyamide 6.

[0023] Furthermore, the antioxidant is one or a mixture of 2,2'-thiobis[ethyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,6-di-tert-butyl-p-cresol and 4,6-bis(octylthiomethyl)-o-cresol.

[0024] The beneficial effects of the present invention are:

[0025] In the present technical solution, the prepared alumina is first compounded with high-crystallinity boehmite and then mixed with porous low-crystallinity boehmite. Under the action of ultrasound, part of the high-crystallinity boehmite / alumina complex enters the pores of the low-crystallinity boehmite to form a boehmite / alumina complex. When applied to thermoplastic plastic materials, part of the thermoplastic plastic material also enters the pores of the low-crystallinity boehmite, thereby preventing the aggregation of the boehmite / alumina complex. When combustion occurs, the thermoplastic plastic forms a denser carbon layer through the framework of the boehmite / alumina complex, thereby blocking heat exchange and improving flame retardant properties. DETAILED DESCRIPTION

[0026] The technical solutions of the present invention are described in detail below through examples. The following examples are merely exemplary and can only be used to explain and illustrate the technical solutions of the present invention, and cannot be interpreted as limiting the technical solutions of the present invention.

[0027] In the following examples of the present application, the raw materials, reagents, equipment, etc. involved, unless otherwise specified, can be obtained by those skilled in the art through commercial channels.

[0028] Preparation Example 1

[0029] (1) Weigh 200 g of basic aluminum chloride, 160 g of potassium hydroxide, 300 g of ether, and 620 g of deionized water, add them to a reaction vessel, and react at 60°C for 3 h to obtain solution A.

[0030] (2) Solution A was filtered, washed, dried, and then calcined at 720°C for 10 h to obtain alumina.

[0031] (3) Weigh a certain amount of high-crystallinity boehmite, place it in a crucible, grind it into powder, and pass it through a 500-mesh sieve to obtain high-crystallinity boehmite powder. Weigh a certain amount of low-crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low-crystallinity boehmite powder.

[0032] (4) Weigh 80 g of alumina, 400 g of high-crystallinity boehmite powder, 500 g of ether, and 700 g of deionized water, add them to a reaction vessel, and react at 60 °C for 6 h to obtain solution B.

[0033] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 60°C for 8 h to obtain a high-crystallinity boehmite / alumina composite.

[0034] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.

[0035] (7) Weigh 50 g of high-crystallinity boehmite / alumina composite powder, 300 g of low-crystallinity boehmite powder, 500 g of ether, and 900 g of deionized water, add them to a reaction vessel, and ultrasonically react at 60°C and 30 kHz for 6 h to obtain solution C.

[0036] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 60°C for 8 h to obtain synergistic flame retardant M1.

[0037] Application Example 1

[0038] (1) Weigh 90 parts of PP, 16 parts of decabromodiphenyl ethane, 4 parts of synergistic flame retardant M1, and 0.1 parts of 2,6-di-tert-butyl-p-cresol, mix and stir evenly to obtain a mixture.

[0039] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material X1.

[0040] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, and the temperature of the sixth temperature zone is 240°C. The head temperature of the twin-screw extruder is 230°C and the screw speed is 220r / min.

[0041] Comparative Example 1

[0042] (1) Weigh 90 parts of PP, 16 parts of decabromodiphenylethane, 4 parts of antimony trioxide, and 0.1 part of 2,6-di-tert-butyl-p-cresol, mix and stir to obtain a mixture.

[0043] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.

[0044] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, and the temperature of the sixth temperature zone is 240°C. The head temperature of the twin-screw extruder is 230°C and the screw speed is 220r / min.

[0045] The performance data of the PP composite materials prepared in the above Application Example 1 and Comparative Example 1 are shown in the following table:

[0046]

[0047] It can be seen from the above table that the flame retardant performance of X1 is better than that of D1, which means that the flame retardant performance of PP is better after adding the synergistic flame retardant M1 of the present invention.

[0048] Preparation Example 2

[0049] (1) Weigh 300 g of basic aluminum chloride, 240 g of potassium hydroxide, 360 g of ether, and 720 g of deionized water, add them to a reaction vessel, and react at 80°C for 5 h to obtain solution A.

[0050] (2) Solution A was filtered, washed, dried, and then calcined at 780°C for 12 hours to obtain alumina.

[0051] (3) Weigh a certain amount of high-crystallinity boehmite, place it in a crucible, grind it into powder, and pass it through a 500-mesh sieve to obtain high-crystallinity boehmite powder. Weigh a certain amount of low-crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low-crystallinity boehmite powder.

[0052] (4) Weigh 80 g of alumina, 400 g of high-crystallinity boehmite powder, 500 g of ether, and 700 g of deionized water, add them to a reaction vessel, and react at 80°C for 8 h to obtain solution B.

[0053] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 80°C for 12 h to obtain a high-crystallinity boehmite / alumina composite.

[0054] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.

[0055] (7) Weigh 80 g of high-crystallinity boehmite / alumina composite powder, 400 g of low-crystallinity boehmite powder, 560 g of ether, and 960 g of deionized water, add them to a reaction vessel, and ultrasonically react at 80°C and 30 kHz for 8 h to obtain solution C.

[0056] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 80°C for 12 h to obtain a synergistic flame retardant M2.

[0057] Application Example 2

[0058] (1) Weigh 110 parts of PBT, 18 parts of decabromodiphenyl ethane, 6 parts of synergistic flame retardant M2, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, 0.2 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and 0.2 parts of antioxidant 4,6-bis(octylthiomethyl)-o-cresol, mix and stir evenly to obtain a mixture.

[0059] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material X2.

[0060] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, and the temperature of the sixth temperature zone is 260°C. The head temperature of the twin-screw extruder is 260°C and the screw speed is 300r / min.

[0061] Comparative Example 2

[0062] (1) Weigh 110 parts of PBT, 18 parts of decabromodiphenylethane, 6 parts of antimony trioxide, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, 0.2 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and 0.2 parts of antioxidant 4,6-bis(octylthiomethyl)-o-cresol, mix and stir evenly to obtain a mixture;

[0063] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2.

[0064] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, and the temperature of the sixth temperature zone is 260°C. The head temperature of the twin-screw extruder is 260°C and the screw speed is 300r / min.

[0065] The performance data of the PBT composite materials prepared in the above Application Example 2 and Comparative Example 2 are shown in the following table:

[0066]

[0067] It can be seen from the above table that the flame retardant performance of X2 is better than that of D2, which means that after adding the synergistic flame retardant M2 of the present invention, the flame retardant performance of PBT is better.

[0068] Preparation Example 3

[0069] (1) Weigh 250 g of basic aluminum chloride, 200 g of potassium hydroxide, 330 g of ether, and 670 g of deionized water, add them to a reaction vessel, and react at 70°C for 4 h to obtain solution A.

[0070] (2) Solution A was filtered, washed, dried, and then calcined at 750°C for 11 hours to obtain alumina.

[0071] (3) Weigh a certain amount of high-crystallinity boehmite, place it in a crucible, grind it into powder, and pass it through a 500-mesh sieve to obtain high-crystallinity boehmite powder. Weigh a certain amount of low-crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low-crystallinity boehmite powder.

[0072] (4) Weigh 100 g of alumina, 450 g of high-crystallinity boehmite powder, 550 g of ether, and 800 g of deionized water, add them to a reaction vessel, and react at 70°C for 7 h to obtain solution B.

[0073] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 70°C for 10 h to obtain a high-crystallinity boehmite / alumina composite.

[0074] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.

[0075] (7) Weigh 50 g of high-crystallinity boehmite / alumina composite powder, 150 g of low-crystallinity boehmite powder, 300 g of ether, and 500 g of deionized water, add them to a reaction vessel, and ultrasonicate at 70°C and 30 kHz for 10 h to obtain solution C.

[0076] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 70°C for 10 h to obtain synergistic flame retardant M3.

[0077] (1) Weigh 100 parts of PE, 17 parts of decabromodiphenyl ethane, 5 parts of synergistic flame retardant M3, 0.1 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and 0.2 parts of antioxidant 2,6-di-tert-butyl-p-cresol, mix and stir evenly to obtain a mixture.

[0078] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material X3.

[0079] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, and the temperature of the sixth temperature zone is 180°C. The head temperature of the twin-screw extruder is 180°C and the screw speed is 300r / min.

[0080] Comparative Example 3

[0081] (1) Weigh 100 parts of PE, 17 parts of decabromodiphenylethane, 5 parts of antimony trioxide, 0.1 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, and 0.2 parts of antioxidant 2,6-di-tert-butyl-p-cresol, mix and stir evenly to obtain a mixture;

[0082] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D3.

[0083] The performance data of the PE composite materials prepared in the above Application Example 3 and Comparative Example 3 are shown in the following table:

[0084]

[0085] It can be seen from the above table that the flame retardant performance of X3 is better than that of D3, which means that after adding the synergistic flame retardant M3 of the present invention, the flame retardant performance of PE is better.

[0086] Preparation Example 4

[0087] (1) Weigh 235 g of basic aluminum chloride, 195 g of potassium hydroxide, 335 g of ether, and 705 g of deionized water, add them to a reaction vessel, and react at 75°C for 3.5 h to obtain solution A.

[0088] (2) Solution A was filtered, washed, dried, and then calcined at 75°C for 11.5 hours to obtain alumina.

[0089] (3) Weigh a certain amount of high-crystallinity boehmite, place it in a crucible, grind it into powder, and pass it through a 500-mesh sieve to obtain high-crystallinity boehmite powder. Weigh a certain amount of low-crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low-crystallinity boehmite powder.

[0090] (4) Weigh 105 g of alumina, 435 g of high-crystallinity boehmite powder, 565 g of ether, and 765 g of deionized water, add them to a reaction vessel, and react at 75°C for 7.5 h to obtain solution B.

[0091] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 75°C for 11.5 hours to obtain a high-crystallinity boehmite / alumina composite.

[0092] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.

[0093] (7) Weigh 50 g of high-crystallinity boehmite / alumina composite powder, 300 g of low-crystallinity boehmite powder, 350 g of ether, and 600 g of deionized water, add them to a reaction vessel, and ultrasonicate at 50°C and 30 kHz for 10 h to obtain solution C.

[0094] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 75°C for 10 h to obtain synergistic flame retardant M4.

[0095] Application Example 4

[0096] (1) Weigh 98.5 parts of PA6, 16.6 parts of decabromodiphenyl ethane, 4.8 parts of synergistic flame retardant M4, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, and 0.2 parts of antioxidant 4,6-bis(octylthiomethyl)-o-cresol, mix and stir evenly to obtain a mixture;

[0097] (2) The mixture obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material X4.

[0098] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 230°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, and the temperature of the sixth temperature zone is 260°C. The head temperature of the twin-screw extruder is 250°C and the screw speed is 320r / min.

[0099] Comparative Example 4

[0100] (1) Weigh 98.5 parts of PA6, 16.6 parts of decabromodiphenylethane, 4.8 parts of antimony trioxide, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, and 0.2 parts of antioxidant 4,6-bis(octylthiomethyl)-o-cresol, mix and stir evenly to obtain a mixture.

[0101] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D4.

[0102] The performance data of the PA6 composite materials prepared in the above Application Example 4 and Comparative Example 4 are shown in the following table:

[0103]

[0104] It can be seen from the above table that the flame retardant performance of X4 is better than that of D4, which means that the flame retardant performance of PA6 is better after adding the synergistic flame retardant of the present invention.

[0105] Preparation Example 5

[0106] (1) Weigh 225 g of basic aluminum chloride, 195 g of potassium hydroxide, 345 g of ether, and 695 g of deionized water, add them to a reaction vessel, and react at 65°C for 4.5 h to obtain solution A.

[0107] (2) Solution A was filtered, washed, dried, and then calcined at 65°C for 10.5 hours to obtain alumina.

[0108] (3) Weigh a certain amount of high-crystallinity boehmite, place it in a crucible, grind it into powder, and pass it through a 500-mesh sieve to obtain high-crystallinity boehmite powder. Weigh a certain amount of low-crystallinity boehmite, grind it into powder, and pass it through a 350-mesh sieve to obtain low-crystallinity boehmite powder.

[0109] (4) Weigh 115 g of alumina, 465 g of high-crystallinity boehmite powder, 555 g of ether, and 735 g of deionized water, add them to a reaction vessel, and react at 78.5 °C for 7.5 h to obtain solution B.

[0110] (5) Solution B was filtered, washed, and placed in a vacuum drying oven at 69°C for 10.5 h to obtain a high-crystallinity boehmite / alumina composite.

[0111] (6) Grind the high crystallinity boehmite / alumina composite into powder, and pass it through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder.

[0112] (7) Weigh 50 g of high-crystallinity boehmite / alumina composite powder, 350 g of low-crystallinity boehmite powder, 400 g of ether, and 740 g of deionized water, add them to a reaction vessel, and ultrasonicate at 65°C and 30 kHz for 10 h to obtain solution C.

[0113] (8) Solution C was filtered, washed, and placed in a vacuum drying oven at 65°C for 10 h to obtain synergistic flame retardant M5.

[0114] (1) Weigh 99 parts of PS, 17.8 parts of decabromodiphenyl ethane, 5.8 parts of synergistic flame retardant M5, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, and 0.1 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, mix and stir evenly to obtain a mixture;

[0115] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material X5.

[0116] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 160°C, the temperature of the second temperature zone is 200°C, the temperature of the third temperature zone is 200°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, and the temperature of the sixth temperature zone is 200°C. The head temperature of the twin-screw extruder is 200°C and the screw speed is 280r / min.

[0117] Comparative Example 5

[0118] (1) Weigh 99 parts of PS, 17.8 parts of decabromodiphenylethane, 5.8 parts of antimony trioxide, 0.1 parts of antioxidant 2,6-di-tert-butyl-p-cresol, and 0.1 parts of antioxidant β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, mix and stir evenly to obtain a mixture;

[0119] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D5.

[0120] The performance data of the PS composite materials prepared in the above-mentioned Application Example 5 and Comparative Example 5 are shown in the following table:

[0121]

[0122] It can be seen from the above table that the flame retardant performance of X5 is better than that of D5, which means that the flame retardant performance of PS is better after adding the synergistic flame retardant M5 of the present invention.

[0123] The above disclosures are only a few specific embodiments of the present application, but the present application is not limited thereto. Any changes that can be conceived by those skilled in the art should fall within the scope of protection of the present application.

Claims

1. A method for preparing a synergistic flame retardant, characterized in that: The following steps are involved: S1. Weigh a certain amount of basic aluminum chloride, potassium hydroxide, ether, and deionized water, add them to a reaction vessel, and react at 60-80°C for 3-5 hours to obtain solution A; S2. Filter solution A, wash, dry, and then calcine at 720-780°C for 10-12 hours to obtain alumina; S3, weighing a certain amount of high crystallinity boehmite, grinding it into powder, and passing it through a 500-mesh sieve to obtain high crystallinity boehmite powder; weighing a certain amount of low crystallinity boehmite, grinding it into powder, and passing it through a 350-mesh sieve to obtain low crystallinity boehmite powder; S4. Weigh a certain amount of alumina, high-crystallinity boehmite powder, ether, and deionized water, add them to a reaction vessel, and react at 60-80° C. for 6-8 hours to obtain solution B; S5. Filter solution B, wash it, and place it in a vacuum drying oven at 60-80° C. for 8-12 hours to obtain a high-crystallinity boehmite / alumina composite; S6. Grinding the high crystallinity boehmite / alumina composite into powder, and passing the powder through a 500-mesh sieve to obtain high crystallinity boehmite / alumina composite powder; S7. Add a certain amount of high crystallinity boehmite / alumina composite powder, low crystallinity boehmite powder, ether, and deionized water to a reaction dish, and ultrasonically react at 60-80° C. for 6-8 hours to obtain solution C; S8. Filter solution C, wash it, and place it in a vacuum drying oven at 60-80° C. for 8-12 hours to obtain a synergistic flame retardant.

2. The method for preparing a synergistic flame retardant according to claim 1, wherein: In step S1, the mass ratio of basic aluminum chloride, potassium hydroxide, ether, and deionized water is (20-30): (16-24): (30-36): (62-72).

3. The method for preparing a synergistic flame retardant according to claim 1, wherein: In step S4, the mass ratio of alumina, high crystallinity boehmite powder, ether, and deionized water is (8-12): (40-50): (50-60): (70-90).

4. The method for preparing a synergistic flame retardant according to claim 1, wherein: In step S7, the mass ratio of high crystallinity boehmite / alumina composite powder, low crystallinity boehmite powder, ether, and deionized water is: (5-10): (30-50): (50-60): (90-100).

5. The method for preparing a synergistic flame retardant according to claim 1, wherein: The ultrasonic reaction in step S7 is 30 KHz.

6. The method for preparing a synergistic flame retardant according to claim 1, wherein: In step S8, the mass ratio of high crystallinity boehmite to low crystallinity boehmite is 1:2-1:

5.

7. An application, characterized in that: Use of the synergistic flame retardant prepared according to any one of claims 1 to 6 in thermoplastic plastic composites.

8. The use according to claim 7, characterized in that The thermoplastic plastic composite material consists of the following components in parts by weight: 90-110 parts of thermoplastic plastic, 16-18 parts of decabromodiphenylethane, 4-6 parts of synergistic flame retardant, and 0.1-0.5 parts of antioxidant.

9. The use according to claim 8, characterized in that The thermoplastic plastic composite material is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate, and polyamide 6.

10. The use according to claim 8, characterized in that The antioxidant is one of 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)ethyl propionate], 2,6-di-tert-butyl-p-cresol and 4,6-bis(octylthiomethyl)-o-cresol or a mixture of several thereof.

Citation Information

Patent Citations

  • Thermally-conductive and flame-retardant composite filler and preparation method thereof

    CN109232990A

  • Method for the production of a finely crystalline boehmite and application of said boehmite as flame retardant in plastics

    US20070217993A1